Crystalloid lysozyme inclusions in Paneth cells of vitamin A-deficient rats - Koch, Martin Jean; Biesalski, Hans-Konrad; Stofft, Eckart; Weiser, Harald; Gabbert, Helmut E.; Dienes, Hans-P.; Schulz-Dobrick, Burkard; Bässler, Karl H. (Cell & tissue research, 1990)
The effect of vitamin A-deficiency on jejunal Paneth cells in rats was investigated. Crystalloid particles were observed in secretion granules of Paneth cells from 6 out of 8 rats with vitamin A-deficiency. The particles were similar to those found in Paneth cells under other experimental conditions. Using an immuno-electron-microscopic technique we demonstrated a clear lysozyme immunoreactivity of these particles. In 2 vitamin A-deficient rats tubular structures have been detected in addition to the crystalloid particles. Crystalloid particles or tubular structures were not detectable in a control group of 8 vitamin A-supplemented rats. The morphological alterations of Paneth cells may be correlated to an impaired local immunity of the intestine during vitamin A-deficiency.
Gesehen am 10.02.2021